Comparative Study on the Accuracy of Terrestrial and Global Gravitational Models (GGMs) Gravity Anomalies for Akure Environs, Ondo State, Nigeria - Ibrahim Olatunji Raufu; Herbert Tata; Korede Samuel Buraimoh (Indonesian Journal of Earth Sciences)
Spherical harmonic expansion is a mathematical method used to describe Earth's gravity field, derived from potential coefficients observed both on Earth's surface and from space. The International Centre for Gravity Earth Models (ICGEM) publishes Global Gravitational Models (GGMs), which require validation using terrestrial data to assess their suitability in specific regions. This study evaluates and compares gravity anomalies derived from five GGMs (EGM 2008, GECO, XGM2019e-2159, SGG-UGM-2, and EIGEN-6C4) with terrestrial gravity data over the Akure area of Ondo State, Nigeria. Gravity values and geodetic coordinates from 23 stations were analyzed. Terrestrial gravity data were sourced from previous field surveys, while GGM data were obtained from the International Centre for Global Earth Gravity Model (ICGEM). The study computed and compared free-air and Bouguer anomalies with mean differences ranging from -1.725 to 6.800 mGal (with standard errors between 1.058 to 1.965 mGal) for free-air anomalies, and -2.107 to 4.546 mGal (with standard errors between 0.773 to 1.041 mGal) for Bouguer anomalies. Statistical analyses revealed that the EGM 2008, GECO, and XGM 2019e-2159 models provided the best-fit with terrestrial measurements. These models can thus serve as reliable alternatives or complements to terrestrial gravity data for geoid determination in the Akure region. The study identifies EGM2008, GECO, and XGM2019e_2159 as the most suitable GGMs for geophysical applications in this area.